PROJECTING GENDER IDENTITY THROUGH METADISCOURSE MARKING: INVESTIGATING WRITERS’ STANCE TAKING IN WRITTEN DISCOURSE - Seyyedrezaie, Zari Sadat; Vahedi, Vahideh Sadat (Universitas Pendidikan Indonesia, 2017)
The present study aimed at investigating gender identity through the expression of interpersonal metadiscourse stance marking. The current study investigated male and female authors' pattern of stance markers utilization, focusing on totally 60 English and Persian articles, and English articles written by Persian speakers. Based on Xu and Longs'(2008) classification, five categories of stance markers (textual, epistemic, attitudinal, deontic and causation) were identified and the frequencies of their occurrences were computed. The differences in each group were investigated separately through running chi-square tests. Regarding English articles, it was found that both male and female writers used the same pattern of stance taking except the epistemic markers. Another finding of this study was that both male and female writers followed the same pattern of stance taking in Persian articles except the deontic ones. In English articles written by Persian speakers, female writers used the same pattern as their native counterparts, while male ones were affected mostly by their native language. Attending to stance taking patterns, this article provides an informative picture which illustrates the common preferences of disciplinary community especially between male and female writers. Hence, the implications of this study can be helpful in academic writing, in assessment, and textbooks.